1968 – The Year of Living Vicariously: The London Whirlwind. (1st December 2018) - Dikerdem, Mehmet Ali
Abstract : This is an essay in critical auto-ethnography in the form of a personal memoire of the experiences in the tumultous year 1968 of a 19-year old from a privileged but political background. Spread across London, Accra, Istanbul, Manchester and New York throughout 1968, the text is a dialogue between selected lived experiences of the time juxtaposed with retrospective political commentary trying to explain contexts, continuities and ruptures. The final section can be read as a reflection on what it means to be of the "'68 generation" half a century on.